Characteristics of the Forest Clove Plant Organ (Syzygium obtusifolium L) Endemic Maluku, Indonesia. Issue 1 (1st January 2023) - Kamsurya, M Y; Ala, A; Musa, Y; Rafiuddin,
Abstract: Forest clove ( Syzygium obtusifolium L.) has not been widely known for its properties and characteristics. To recognize them properly, deeply, and thoroughly, efforts are required to characterize the morphological characteristics of the main organs. The research aims to reveal the morphological characteristics of the main organ ( cormus ) of the forest clove plant, which include roots, stems, and leaves. The research was conducted on the island of Ambon, Maluku, Eastern Indonesia, for five months from May-September 2020. This research is survey research, data collection using a questionnaire arranged according to IPGRI criteria. The list of questions was filled indirectly to the field. The results showed that the root system of the forest clove plant was a taproot consisting of primary roots followed by lateral roots (primary root branches), secondary, tertiary, and quartet-like roots which were then overgrown with root hairs. Lateral root branches are large, and in subsequent root branches, the size is smaller but in increasing numbers. The trunk is round, with a diameter ranging from 12.5-25.5 cm, the surface of the trunk is rough brown and grayish, accompanied by black spots. The branching pattern is intensive with the main branching angles included in the medium category, meaning that the angles formed with the main rods range from 45-90o. The leaves of the forest clove plant are oblong with a length ranging from 15-25.5 cm and a width of 5.5-9.5 cm. The correction factor to determine leaf area is 0.65, therefore the leaf area ranges from 53.63 to 157.46 cm2. The shape of the base of the leaf is tapered, the angle of the petiole is sharp (<45o). The nature of the tips of the leaves is rather hard, the texture of the leaves is strong, the edges are flat, and the color of the leaves is dark green (green 139 A).